Character assassination and reputation management theory and applications - Shiraev, Eric 1960-; Keohane, Jennifer A.; Icks, Martijn (Routledge, 2022)
This lively book offers the first comprehensive examination of character assassination. In modern politics as well as in historical times, character attacks abound. Words and images, like psychological weapons, have sullied or destroyed numerous individual reputations. How does character assassination "work" and when or why does it not? Are character attacks getting worse in the age of social media? Why do many people fail when they are under character attack? How should they prevent attacks and defend against them? Moving beyond discussion corporate reputation management and public relations canons, Character Assassination and Reputation Management is designed to help understand, critically analyze, and effectively defend against such attacks. Written by an international and interdisciplinary team of experts, the book begins with a discussion of theoretical and applied features of the "five pillars" of character assassination: (1) the attacker, (2) the target, (3) the media, (4) the audience, and (5) the context. The remaining chapters present engaging in-depth discussions and case studies suitable for homework and class discussion. These cases include: Historic figures Leaders from modern times Women in politics US Presidents World leaders Political autocrats Democratic leaders Scientists Celebrities Featuring an extensive glossary of key terms, critical thinking exercises, and summaries to encourage problem-based learning, Character Assassination and Reputation Management will prove invaluable to the undergraduate and postgraduate students in communication, political science, global affairs, history, sociology, and psychology departments"--